The Evaluation of Usability and Website Development using Cognitive Walkthrough, Performance Measurement, and System Usability Scale - I Gusti Putu Yada Giri; Luh Joni Erawati Dewi; I Made Gede Sunarya (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
The website of Social Affairs, Empowerment, and Child Protection in Bali is one of the information media used to fulfill one of the Service's requirements in implementing the Law on Public Information Disclosure. The initial observation results showed that there has never been a usability evaluation related to the website. In addition to this, according to an initial survey of 55 respondents from the general public and service information technology staff, the results obtained were (1) 69% of respondents stated that the website for the Office of Social Affairs, Women's Empowerment and Child Protection of the Province of Bali had an unattractive appearance, (2) as many as 67% of respondents stated that the website was still not good at placing and writing menus, (3) 67% of respondents stated that the website could not provide comfort when browsing, and (4) 95% of respondents stated that the display and contents of website content were still lacking and need to be developed. Based on the results of the interviews and surveys conducted, it is necessary to carry out an evaluation to find out more about the development of the website for the Bali Provincial Office of Social Affairs, Women's Empowerment and Child Protection. Therefore an evaluation was carried out on the website of Social Affairs, Women's Empowerment, and Child Protection of Bali using the Cognitive Walkthrough, Performance Measurement, and System Usability Scale (SUS) evaluation techniques. The research resulted in the following conclusions. (1) The website development for the Provincial Office of Social Affairs, Women's Empowerment, and Child Protection uses the Incremental method to produce a website with a more dynamic and modern appearance but still minimalist so that it does not interfere with the view of the website visitors and remains focused on content so that it is comfortable to view and read. (2) The performance measurement method evaluation results showed that the website is included in the effective and efficient category. The results showed that the working time for the beginner and the proficient group was short, the average for the proficient group was 17.4 seconds, and the beginner was 17.56 seconds. (3) Recommendations from the results of the usability evaluation of the Bali Provincial Office of Social Affairs, Women's Empowerment, and Child Protection using the Cognitive Walkthrough method are included in the successful category. Research showed that 100% of respondents completed the task scenario perfectly without any failures or errors. (4) Satisfaction of website users, when evaluated using the SUS method, gets an average score of 92.36 which is above the standard score of 68, so it can be concluded that respondents are very satisfied using the website for Social Affairs, Women's Empowerment and Child Protection of the Bali Province.